Glycoform-independent prion conversion by highly efficient, cell-based, protein misfolding cyclic amplification - Moudjou, Mohammed (Sci Rep, 2016)
Prions are formed of misfolded assemblies (PrP(Sc)) of the variably N-glycosylated cellular prion protein (PrP(C)). In infected species, prions replicate by seeding the conversion and polymerization of host PrP(C). Distinct prion strains can be recognized, exhibiting defined PrP(Sc) biochemical properties such as the glycotype and specific biological traits. While strain information is encoded within the conformation of PrP(Sc) assemblies, the storage of the structural information and the molecular requirements for self-perpetuation remain uncertain. Here, we investigated the specific role of PrP(C) glycosylation status. First, we developed an efficient protein misfolding cyclic amplification method using cells expressing the PrP(C) species of interest as substrate. Applying the technique to PrP(C) glycosylation mutants expressing cells revealed that neither PrP(C) nor PrP(Sc) glycoform stoichiometry was instrumental to PrP(Sc) formation and strainness perpetuation. Our study supports the view that strain properties, including PrP(Sc) glycotype are enciphered within PrP(Sc) structural backbone, not in the attached glycans.